Self‐aggression, reactive aggression, and spontaneous aggression: Mediating effects of self‐esteem and psychopathology. Issue 4 (31st January 2019) - Otte, Stefanie; Streb, Judith; Rasche, Katharina; Franke, Irina; Segmiller, Felix; Nigel, Stefanie; Vasic, Nenad; Dudeck, Manuela
Abstract: This study examined whether the associations between self‐aggression and different forms of externalized aggression (reactive and spontaneous aggression) are influenced by self‐esteem and current psychopathological symptoms. For this purpose, we asked 681 participants from the general population (GP) and 282 general psychiatric patients (PPs) to answer the German versions of the Short Questionnaire for Assessing Factors of Aggression (K‐FAF), the Multidimensional Self‐Esteem Scale (MSWS), and the Brief Symptom Inventory 25 Forensic (BSI‐25‐F). Statistically, we performed descriptive and mediation analyses. Our findings indicated that in both samples the association between self‐aggression and reactive aggression was mediated by self‐esteem but not by current psychological problems. The association between self‐aggression and spontaneous aggression was mediated by self‐esteem in the GP sample and by psychopathological symptoms in the PP sample. We conclude that when examining the association between self‐aggression and externalized aggression it is important to consider the various subtypes of externalized aggression and differences between populations.